Religio-philosophical discourses in the Mediterranean world: from Plato, through Jesus, to late antiquity - Klostergaard Petersen, Anders; Kooten, Geurt Hendrik van (Biblical Studies, Ancient Near East and Early Christianity E-Books Online$aCollection 2017, 2017)
Preliminary Material /Anders Klostergaard Petersen and George van Kooten -- Introduction: The Religion and Philosophy Debate in a New Key /Anders Klostergaard Petersen and George van Kooten -- Plato’s Philosophy – Why Not Just Platonic Religion? /Anders Klostergaard Petersen -- Platonic Piety: ‘Putting Humpty Dumpty Together Again’ /Frisbee Sheffield -- The Real Euthyphro Problem, Solved /Nicholas Denyer -- Religion, Philosophy, and the Demons in Between /Lars Albinus -- Philosophical Traces in the Sibylline Oracles /Helen Van Noorden -- Philosophy and Religion and Their Interactions in 4 Maccabees /Anders Klostergaard Petersen -- The Rapprochement of Religion and Philosophy in Ancient Consolation: Seneca, Paul, and Beyond /Christoph Jedan -- Jesus among the Philosophers: The Cynic Connection Explored and Affirmed, with a Note on Philo’s Jewish-Cynic Philosophy /Bernhard Lang -- The Last Days of Socrates and Christ: Euthyphro, Apology, Crito, and Phaedo Read in Counterpoint with John’s Gospel /George van Kooten -- Criticism of Verbosity in Ancient Philosophical and Early Christian Writings: Jesus’ Critique of the ‘Polylogia’ of Pagan Prayers (Matthew 6:7) in its Graeco-Roman Context /Daniele Pevarello -- Christians According to Second-Century Philosophers /Simon Gathercole -- Epictetus’ Views on Christians: A Closed Case Revisited /Niko Huttunen -- Plotinus, Origenes, and Ammonius on the ‘King’ /Harold Tarrant -- Neo-Platonic Readings of Embodied Divine Presence: Iamblichus and Julian /Ilinca Tanaseanu-Döbler -- Index of Ancient Sources /Anders Klostergaard Petersen and George van Kooten -- Index of Modern Authors /Anders Klostergaard Petersen and George van Kooten -- Index of Subjects /Anders Klostergaard Petersen and George van Kooten.